Perancangan Modular Furniture untuk Food Truck Penjual Makanan Indonesia - Chetlyne Stefany Soekanto; I Gusti Ngurah Ardana; Sherly de Yong (Intra, 2016)
Food and beverage industry growth in Indonesia continues to develop, and need to be traded in location with dense occupants so that the business can be profitable. This has resulted in the emergence of the mobile system, as selling methods are much in demand today. Food vendors are mobile, requiring a furniture design that can support the activity of cooking and selling on a vehicle. By using Kembel design method, through the process of understanding, compressing, processing the data using descriptive analysis technique, concept, prototypes, testing and persuasion. The results of the design is a modular furniture that can be arranged as desired with a construction system devoted for installation in vehicles and some other alternative such as fast food design, food combination design, cooked food design, traditional food snack and Indonesia’s coffee drinks.